An examination of the effectiveness of race-based distributive justice in South Africa - Rajaram, Rajitha (My University, 2023)
In this research project, I argue that the adoption of race-based distributive justice in South Africa (SA) has not benefited the groups that are targeted in the policy. To achieve this, I set the scene with the historical landscape of SA, as a precursor to understanding and appreciating the context. In adopting race-based justice, SA created an alternative mechanism to maintain a hold over individuals and has not created a fair environment that adequately supports just distribution or restorative justice. The patterns by which distributions are designed and implemented have created dependencies that prevent individuals from emancipating themselves sufficiently to live autonomous lives. I intend to assert that the quality of distributions is poor and contribute to restricting previously disadvantaged individuals from fully exploring their own potential in attaining economic emancipation and becoming fruitful contributors to society as a whole. This cycle of oppression also has a negative impact on the dignity and self-worth of previously disadvantaged groups. Redistribution is intended to compensate or restore that which people have lost, in this instance, due to the apartheid legislation and historical suffering. Robert Nozick’s entitlement theory focuses on historical injustice and is an appropriate setting for the exploration of this research. The three principles of the entitlement theory guide the need and the nature of the appropriate compensation. I further purport that the alternative approach of class-based distributive justice is more focused and has a wider reach in the audience it intends to target than race-based distributions. The class-based approach has a greater impact on the lives of citizens that are in need and deserving of restitution, with the primary focus being upliftment of individuals at a more holistic level and, in doing so, has a positive impact on the lives and dignity of the people. My approach for this research includes interrogation of the applicable legislation, namely the Broad-Based Black Economic Empowerment (BBBEE) Act and its related impact on previously marginalised citizens. BBBEE and other similar legislation are devised to right the wrongs of the apartheid legislation. Apartheid deprived all black citizens of economic exposure and opportunity to accumulate wealth, and the dawn of democracy provided an opportunity for the wrong to be corrected.
A dissertation submitted in partial fulfilment of the requirements for the degree of Master of Artsin Applied Ethics for Professionals to the Faculty of Humanities, University of the Witwatersrand, 2023
Keywords: Race-Based Distributive Justice; Historical landscape